Experimental Works for Determine Manning’s Coefficient Roughness in Open Channels - Hadi, ZOHUL Abdul; HAMDAN, AHMED N. A. (Basrah Journal for Engineering Sciences, 2008)
A Laboratory study was conducted in a tilting flume, 0.6 m wide and 3.0 m long to study the effect of regular and irregular bed material on the resistance to the flow of different bed material. The results show that the maximum increase in Manning’s roughness coefficient happens when the bed is regular and the maximum reduction in Manning roughness coefficient happens when the bed is irregular.